Electromagnetic Information Leakage and Countermeasure Technique Translated by Liu Jinming, Liu Ying, Zhang Zidong, Liu Tao - Liu, Taikang; Li, Yongmei; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents a model of electromagnetic (EM) information leakage based on electromagnetic and information theory. It discusses anti-leakage, anti-interception and anti-reconstruction technologies from the perspectives of both computer science and electrical engineering. In the next five years, the threat posed by EM information leakage will only become greater, and the demand for protection will correspondingly increase.The book systematically introduces readers to the theory of EM information leakage and the latest technologies and measures designed to counter it, and puts forward an EM information leakage model that has established the foundation for new research in this area, paving the way for new technologies to counter EM information leakage. As such, it offers a valuable reference guide for all researchers and engineers involved in EM information leakage and countermeasures.
Introduction -- Introduction EM information fundamental and leakage mechanism -- EM information interception and reproduction -- EM information leakage countermeasure technique -- EM information leakage countermeasure material -- Computer EM information leakage and countermeasure -- EM information Data processing -- EM information leakage testing -- Standards of EM information leakage and countermeasure.
Keywords: Telecommunication; Computers; Data structures (Computer science).; Information theory; Security systems; Microwaves, RF Engineering and Optical Communications; Computer Hardware; Data Structures and Information Theory; Security Science and Technology